"I was 15 when I started doing drugs with my dad": Victimization, Social Determinants of Health, and Criminogenic Risk Among Women Opioid Intervention Court Participants - Morse, Diane S. (Journal of interpersonal violence, 2022)
The presence and severity of childhood and adult victimization increase the likelihood of substance use disorder (SUD), crimes, antisocial behaviors, arrests, convictions, and medical and psychiatric disorders among women more than men. These problems are compounded by the impact of social determinants of health (SDH) challenges, which include predisposition to the understudied, dramatic increase in opioid dependence among women. This study examined victimization, related SDH challenges, gender-based criminogenic risk factors for female participants, and public health opportunities to address these problems. We recruited women from the first national Opioid Intervention Court, a fast-track SUD treatment response to rapidly increasing overdose deaths. We present a consensual qualitative research analysis of 24 women Opioid Intervention Court participants (among 31 interviewed) who reported childhood, adolescent, and/or adult victimization experiences in the context of substance use and recovery, mental health symptoms, heath behaviors, and justice-involved trajectories. We iteratively established codes and overarching themes. Six primary themes emerged: child or adolescent abuse as triggers for drug use; impact of combined child or adolescent abuse with loss or witnessing abuse; adult abduction or assault; trajectory from lifetime abuse, substance use, and criminal and antisocial behaviors to sobriety; role of friends and family support in recovery; and role of treatment and opioid court in recovery, which we related to SDH, gender-based criminogenic factors, and public health. These experiences put participants at risk of further physical and mental health disorders, yet indicate potential strategies. Findings support future studies examining strategies where courts and health systems could collaboratively address SDH with women Opioid Intervention Court participants.